2002
DOI: 10.1034/j.1399-3038.2002.01005.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a parental training program for the management of childhood atopic dermatitis

Abstract: Atopic dermatitis (AD) in childhood is a common disease with prevalence rates as high as 20%. Its early onset in infancy and its chronic relapsing course puts a special burden on families. Supporting parents in dealing with the management of AD presents a challenge for physicians. The objective of this study was to determine the effect of a structured parental training program on managing AD in children. Two-hundred and four families participated in a prospective, randomized controlled trial. Children (5 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
205
0
14

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(227 citation statements)
references
References 16 publications
1
205
0
14
Order By: Relevance
“…Six new studies reported since 2000 [350][351][352][353][354][355] have looked at eczema education sessions for children, parents and carers, with all using slightly different approaches. Overall, the interventions in this section are quite diverse with regard to the components and intensity of the interventions, with time spent on the education ranging from 15 minutes to 2 weeks.…”
Section: (See Appendix 3)mentioning
confidence: 99%
See 2 more Smart Citations
“…Six new studies reported since 2000 [350][351][352][353][354][355] have looked at eczema education sessions for children, parents and carers, with all using slightly different approaches. Overall, the interventions in this section are quite diverse with regard to the components and intensity of the interventions, with time spent on the education ranging from 15 minutes to 2 weeks.…”
Section: (See Appendix 3)mentioning
confidence: 99%
“…A study by Staab and colleagues 352 in 2002 looked at a parental training programme. Ninety-three participants received 2-hour training sessions (once a week for 6 weeks) and 111 participants did not receive any training.…”
Section: (See Appendix 3)mentioning
confidence: 99%
See 1 more Smart Citation
“…Its early onset in infancy and chronic relapsing course puts special burden on their families 1 . Children with AD often have behavioral problems such as increased dependency, fearfulness and sleep difficulties 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Children with AD often have behavioral problems such as increased dependency, fearfulness and sleep difficulties 2 . Supporting parents in dealing with the management of AD presents a challenge for physicians 1 . Educational programs for parents and patients with AD have been established in the last ten years in different European countries [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%